PENGELOLAAN KEUANGAN USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) PADA USAHA BUMBUNG INDAH KOTA PAREPARE (ANALISIS MANAJEMEN KEUANGAN SYARIAH) - Muhammad Suras; Darwis; Syahriyah Semaun (Moneta: Jurnal Manajemen & Keuangan Syariah, 2024)
This research aims to determine the financial management implemented by the Bumbung Indah business in Parepare City as well as the supporting and inhibiting factors in its financial management which are then analyzed using sharia financial management. This research uses a qualitative method with a case study approach. The collected data is analyzed by checking the validity of the data, classifying, verifying and drawing conclusions. Testing the validity of the data used is the triangulation technique and the triangulation method method. The results of the research show that the financial management of the Bumbung Indah business is not yet completely complete because the planning, recording and financial control have been done well, but at the time of financial reporting it was not reported completely every month in the 2020-2022 period. The supporting factors for Bumbung Indah business financial management are the awareness of MSME players and the existence of the Shop Program application. Factors inhibiting financial management are lack of knowledge, separating personal money from business money, and discipline in financial recording. Sharia financial management analysis of Bumbung Indah's business financial management is in accordance with sharia principles